Paxlovid (Nirmatrelvir/Ritonavir): A new approach to Covid-19 therapy? - Hashemian, Seyed Mohammad Reza; Sheida, Amirhossein; Taghizadieh, Mohammad; Memar, Mohammad Yousef; Hamblin, Michael R.; Bannazadeh Baghi, Hossein; Sadri Nahand, Javid; Asemi, Zatollah; Mirzaei, Hamed (Biomedicine & pharmacotherapy, 2023)
Despite the need for novel, effective therapeutics for the COVID-19 pandemic, no curative regimen is yet available, therefore patients are forced to rely on supportive and nonspecific therapies. Some SARS-CoV-2 proteins, like the 3 C-like protease (3CLpro) or the major protease (Mpro), have been identified as promising targets for antiviral drugs. The Mpro has major a role in protein processing as well as pathogenesis of the virus, and could be a useful therapeutic target. The antiviral drug nirmatrelvir can keep SARS-CoV-2 from replicating through inhibiting Mpro. Nirmatrelvir was combined with another HIV protease inhibitor, ritonavir, to create Paxlovid (Nirmatrelvir/Ritonavir). The metabolizing enzyme cytochrome P450 3 A is inhibited by ritonavir to lengthen the half-life of nirmatrelvir, so rintonavir acts as a pharmacological enhancer. Nirmatrelvir exhibits potent antiviral activity against current coronavirus variants, despite significant alterations in the SARS-CoV-2 viral genome. Nevertheless, there are still several unanswered questions. This review summarizes the current literature on nirmatrelvir and ritonavir efficacy in treating SARS-CoV-2 infection, and also their safety and possible side effects. [Display omitted] •Nirmatrelvir/ritonavir is used as an emergency therapy for mild-to-moderate COVID-19.•Nirmatlavir can inhibit the main protease (Mpro) of SARS-CoV-2.•Ritonavir increases plasma concentrations of nirmatrelvir by targeting CYP3A4.•Interaction between nirmatrelvir/ritonavir and other drugs needs more studies.•Paxlovid's low cost and easy administration can become it’s a tool in fighting virus.